THEME TYPES ANALYSIS OF PARATACTIC CLAUSE COMPLEXES OF LUKE CHAPTER 17 OF THE ENGLISH STANDARD VERSION BIBLE IN THE ESV.org - Siahaan, Sahat Taruli; Simorangkir, Samuel B.T (ELT (English Language Teaching Prima Journal), 2023)
This aim’s study is to analyse the textual function such as theme types of the biblical text of Luke Chapter 17 of the English Standard Version in the site ESV.org. The data of this research are English clauses of English Standard Version (ESV) that comprises 56 clauses from 5 subtopics of Luke Chapter 17. The data source for this research is a biblical version text of English Standard Version (ESV) of Edition 2016 in the online bible site ESV.org. The biblical chapter of Luke 17 comprises 5 subtitles, that is (1) Temptations to Sin, (2) Increase Our Faith, (3) Unworthy Servants, (4) Jesus Cleanses Ten Lepers, and (5) The Coming of the Kingdom. The theory used in this study is of Halliday's Systemic Functional Linguistics. The technical model approach of the data analysis of this research is of Eggins (2004: 314; 318-320) regarding (1) four types of theme (Eggins, 2004: 300-316); (2) theme type analysis in declarative sentence; (3) theme type analysis in elliptical declaratives; (4) theme type analysis in WH-interrogatives; (5) theme type analysis in imperatives; (6) theme in paratactic clause complexes; (7) theme in hypotactic clause complexes; and (8) 3 types of adjuncts (Eggins, 2004: 160-170). Based on the results of research data analysis, the results of this study are: 1) four types of theme of paratactic clause complexes of Luke 17 in the English Standard Version (ESV) Bible revised Edition 2016, that is (1) the topical themes with 33 items (62%), (2) the interpersonal theme with 4 items (7%), (3) the textual theme with 13 items (24%) and (4) the multiple themes with 3 items (7%); 2) the topical themes (62%) is the dominant type of theme of paratactic clause complexes on biblical text of Luke Chapter 17 of the English Standard Version (ESV) Bible in the ESV.og. Keywords: theme_types_analysis; paratactic_clause_complexes; Luke_Chapter_17; English_Standard_Version_Bible; the_ESV.org